Identification of Candida species in formalin fixed, paraffin wax embedded oral mucosa by sequencing of ribosomal DNA. Issue 1 (February 1996) - Williams, D W; Wilson, M J; Lewis, M A O; Potts, A J C
Abstract : Aim —To identify Candida species in formalin fixed, paraffin wax embedded tissue by sequencing candidal rDNA. Methods —Target rDNA sequences were amplified by polymerase chain reaction (PCR) from fresh isolates of Candida and from 18 preserved oral mucosal tissue samples (16 cases of chronic hyperplastic candidiasis and two fibroepithelial polyps), shown histologically to contain Candida. Identification of Candida species within tissue was based on a comparison of the rDNA sequences obtained with those from the fresh isolates of Candida and those present in the GenBank database. Results —The PCR products obtained from 12 of the 18 tissue specimens studied were characteristic of Candida albicans. In two of these cases a second, larger PCR product was obtained and these sequences were characteristic of Candida glabrata. Conclusions —Candidal DNA was amplified successfully from formalin fixed, paraffin wax embedded tissue. Sequencing of the PCR product enabled identification of the Candida species present.